Ungrading: Why Rating Students Undermines Learning (and What to Do Instead) - Lori M Costello (Journal of Applied Communications, 2023)
Book review of Ungrading: Why Rating Students Undermines Learning (and What to Do Instead), edited by Susan D. Blum with a foreword by Alfie Kohn
Keywords: Ungrading; Grading; Assessment; Professional Development